Trends in urine lead and associated mortality in US adults: NHANES 1999–2018 - Wang, Qiong; Wu, Jing; Dong, Xiaoqun; Niu, Wenquan (Frontiers in Nutrition, 2024)
Objectives This study aimed to describe the trends of urine lead among US adults aged ≥45 years and to explore its association with all-cause and disease-specific mortality. Methods This study enrolled 9,669 participants from the National Health and Nutrition Examination Survey, 1999–2018. Trends in urine lead were described by logistic regression analysis using the survey cycle as a continuous variable. Cox proportional hazard regression analyses were used to quantify the association between urine lead and mortality. Results There was an obvious decline in urine lead concentrations from 1.203 μg/L (95% confidence interval [CI]: 1.083–1.322) in 1999–2000 to 0.478 μg/L (95% CI: 0.433–0.523) in 2017–2018, and this decline was statistically significant (P < 0.001). Referring to the first tertile of urine lead concentrations, risk magnitude for all-cause mortality was significantly and linearly increased after adjustment (P = 0.026 and 0.020 for partially and fully adjusted models, respectively), and significance was attained for the comparison of the third vs. first tertile after full adjustment (hazard ratio [HR]: 1.17, 95% CI: 1.01 to 1.35). Treating urine lead continuously, the risk for all-cause mortality was statistically significant (HR: 1.18 and 1.19, 95% CI: 1.01 to 1.39 and 1.00 to 1.40 for partially and fully adjusted models). For cardiovascular disease-specific and cancer-specific mortality, there was no hint of statistical significance. Conclusions Our findings indicated that urine lead exhibited a declining trend from 1999–2000 to 2017–2018 in US adults aged ≥45 years, and high urine lead was a significant and independent risk factor for all-cause mortality.